Realistic Non-Gaussian Receivers for Long Distance Continuous-Variable Quantum Key Distribution - Lacerda, Joás J.; Melo, Lucas F.; Tacla, Alexandre B. (Anais do Workshop de Redes Quânticas (WQuNets), 2026)
Reception strategies based on non-Gaussian detectors can be used to improve the performance of various quantum information processing tasks. In this work, we investigate the performance of two non-Gaussian receivers with imperfect detectors for long distance CV-QKD protocol. We show that both receivers outperform the ideal homodyne detection scheme even under realistic conditions, providing a robust alternative for enhancing long-distance CV-QKD.